Bukovina - povezave med kakovostjo dreves, hlodovine in žaganega lesa - Jurij Marenče (Slovenian Forestry Institute, 2016)
The research addresses beech wood, from a standing tree to sawn wood. It focuses on the quality evaluation of individual trees and its impact on the later products made of the respective wood. For the needs of observing the quality of standing trees, the current 5-class scale for quality evaluation of the Slovenia Forest Service (SFS) was used. To evaluate the wood assortment, the SIST EN 1316-1:2013 standard was applied, while the evaluation of sawn wood was performed as per the rules of the European Organisation of the Sawmill Industry (EOS). On the basis of the sample of evaluated and eventually harvested trees, the correlations between the quality of trees, roundwood products made of them and the quality of final sawn products were established. The sample equally included trees of all five quality classes. The production of wood assortment provided the most logs of B quality (51%) and the highest quantity of sawn wood of EOS-C quality (52%). Beech trees of excellent quality provided 35% of the wood assortment of highest quality and these provided 8% of the sawn wood of the highest quality. The key criteria for the classification by quality were covered knots for forest products and dead and unsound knots for sawn wood.